Communication Skill in Selling and Salespersons' Self-efficacy in Insurance Business - Dewi, Desak Nyoman Arista Retno; Wimbarti, Supra (Faculty of Psychology, Universitas Surabaya, 2011)
The purpose of this research was to measure salesperson’s self-efficacy and communication skills in selling process based on the communication training given. The subjects in this research were insurance salespersons who deal directly with consumers (financial advisor) in selling life insurance products. The research design was an experimental design with pretest-posttest control group, using communication training on one group (experimental group) and not in the other group (control group). The data collection conducted using interviews and questionnaires then processed using mixed ANOVA analysis. Based on the results (p < .05) it is revealed that there is a difference of self-efficacy between the experimental group (N = 22) and control group (N = 22) during pre-and post communication training (F = 9.910), where the increase of self-efficacy in the experimental group after post communication training is higher. Penelitian ini dilakukan untuk mengukur keyakinan diri wiraniaga terhadap kemampuan komunikasi yang dimilikinya dalam melakukan proses menjual. Subyek pada penelitian ini adalah wiraniaga asuransi yang berhadapan langsung dengan konsumen (financial advisor atau penasehat keuangan) dalam memasarkan produk asuransi jiwa. Penelitian ini merupakan penelitian eksperimen dengan rancangan pretest-posttest control group, dengan pemberian pelatihan komunikasi pada salah satu kelompok (kelompok eksperimen) dan tidak pada kelompok yang lain (kelompok kontrol). Pengambilan data dilakukan menggunakan wawancara dan kuesioner, dan hasil akan diolah menggunakan analisis anava campuran (mixed anova). Berdasarkan hasil olah data (p < ,05) diketahui bahwa terdapat perbedaan keyakinan diri antara kelompok eksperimen (N = 22) dan kelompok kontrol (N = 22) pada saat pra dan pasca pelatihan komunikasi (F = 9.910), dimana peningkatan keyakinan diri pada kelompok eksperimen pasca pelatihan komunikasi lebih tinggi.